Geomorphology, beach classification and seasonal morphodynamic transition of a Mediterranean gravel beach (Sardinia, Gulf of Cagliari). Issue 2 (3rd July 2019) - Buosi, Carla; Ibba, Angelo; Passarella, Marinella; Porta, Marco; Ruju, Andrea; Trogu, Daniele; De Muro, Sandro
ABSTRACT: This paper presents an innovative multi-thematic map (1:2500) that integrates morpho-sedimentological data, hydrodynamic processes, seasonal morphodynamic transitions and the distribution of the benthic habitat of a Mediterranean microtidal, wave-dominated gravel beach system. It is part of a larger cartography of coastal areas, and is based on an interdisciplinary sea-land approach that is applicable worldwide and aims to facilitate coastal management practices and future scientific research. The applications to coastal management include: the facilitation of coastal vulnerability assessments; easy-to-access, up-to-date digital geospatial data; and baseline studies for the future assessment and monitoring of environmental changes. The main environmental features that control the marine processes of this gravel beach appear to be linked to geological and morphological contexts such as the presence of the river mouth, the outcropping of a beach-rock along the coastline, the deposition of gravelly sediment in the beachface and the seagrass cover.